Edukasi Kesadaran Hukum Pada Anak Sejak Usia Dini - Erniyianti Erniyianti; Darwis Anatami (PT. ALHAFI BERKAH INDONESIA, 2023)
Legal awareness needs to be fostered in children, starting from the smallest things, so that children understand and are aware of the rules that apply. Children who understand the rules will avoid conflicts and will not deviate when they enter the community. Educational activities are carried out by informing children through concrete examples of violations of the law and the consequences of breaking the law. This activity is carried out at Al Jupri Orphanage Sekupang Batam. Juvenile delinquency is when children commit bad acts that are against the law. Punishing children for such acts can have a negative impact on their mental growth in the future. It can make them feel scared, worried, and have difficulty sleeping or eating. They may also feel anxious, cry or feel ashamed. This happens because of the criminal justice process, from pre-trial to trial.